Smart Sensing Fluid Flow Device for Mid Stream Process in Oil and Gas Industry - Khushal Khan Kakar; Naqeeb Ullah; M. Salman; M. Atal (Center of Techonolgy (COT), Engineering Faculty, Hasanuddin University, 2025)
In petroleum industries the storage tanks have a real problem of handling and management of fuel quantity. Various devices are used to monitor fuel quantity in storage tanks or boozers, such as flow sensors, level sensors, float switches, analog meters, most commonly probes and manuals. In this regard, we propose digital system to find out the amount of fuel in liters or milliliters in the storage tank.Main objective of this project is to develop a digital display which portrays the precise quantity of fuel being poured into a storage tank or fuel container. This display will help to verify the amount of fuel filled at petrol stations. Currently, the manual process of recording fuel readings is time-consuming and tedious. By implementing this proposed system, customers will save time by receiving an exact reading without the need for double-checking the tank or container. Lately, there have been frequent reports of fuel station fraud, where stations have pumps that display an inflated amount of fuel filled, while the actual quantity poured into the customer's vehicle is much less. In Pakistan, most cars are equipped with analog fuel meters, which do not provide an accurate measure of the fuel level or allow customers to verify the amount of fuel filled at a station.